Eosinophilic Cellulitis After Honeybee Sting - Hsing-Lin Lin; Jiun-Nong Lin; Chao-Wen Chen; Liang-Chi Kuo; Wei-Che Lee (Journal of the Formosan Medical Association, 2009)
Stings by honeybees are not uncommon and most cases cause pain but no significant medical problems. Some patients, however, have lethal complications such as acute anaphylactic shock. Cellulitis caused by honeybee sting is very rare and can be a late complication in some patients. We report a 45-year-old female patient who was stung by a honeybee, and whose right forearm showed progressive swelling with bullous formation after the sting. She was sent to our emergency department with the diagnosis of right hand cellulitis. After treatment with antibiotics for 5 days, the lesions showed no response. Then, systemic steroid was used and the lesion gradually resolved. Diagnosis of Wells' syndrome was made according to clinical appearance, course and characteristic histopathological findings.